PEMANFAATAN INTERNET SEBAGAI MEDIA AKSES INFORMASI DALAM KONTEK HMC (Handphone Mediated Communication) DI KALANGAN MAHASISWA UIN STS JAMBI - Rum, Muhammad (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2017)
This article aims to know the internet exploiting through handphone media to access informtion that used by the students of the state Islamic university Sulthan Thaha Saifuddin of Jambi. This result of research has depicted that; firstly, the orient of students in exploiting handpone in framework of self development ; to support the academic activity ( lesson and research), to add the knowledge, experience, and pass the time with the entertainment amusement information. Secondly, the students’s motivation of the state Islamic university Sulthan Thaha Saifuddin of Jambi in exploiting internet as communications media include; inquiring motif namely motivation to know the new things can add knowledge, to think sistimaticly, to have construction idea, and to add the empirical experience; to motivate to compet profesionally and percepcionist, to have effectivness learning method; to have social integration and to get appreciation from academic society. Thirdly, the students’s target to exploit handphone as communications media are; diversion namely to secede from some problems, medium of emotion release; personal relationship namely friendship, social benefit, wide assocciation, firmness contact with the family and others; personal identity namely x'self reference, eksplorasi reality, reinforcement assess, wish to strengthen the self identity, belief, individual status and stability. Fourthly, Form and method of information seeking by student through handphone as communications media through article, PDF, while browsing machine is used generally the Google and Yahoo. The browsing is done only download. Finally, the students’s expectation in exploiting internet for the ptoses of x'self development are; good behaviour namely appearance of student behaviour which like to read, like to discuse to hit the knowledge dynamics in so many angle; corner, to investigate the truth performing of research, like the loran or solitary than talking with others in fad.